The relationship between social participation and quality of life in individuals with traumatic brain injury - Toshinori Watanabe; Megumi Suzuki; Kouji Yamada; Naoki Aizu; Kikuo Ota (Fujita Medical Journal)
Objective: To elucidate the relationship between social participation and quality of life (QOL) in patients with traumatic brain injury.